2017
DOI: 10.1002/2017ja024268
|View full text |Cite
|
Sign up to set email alerts
|

Energetic particle loss through the magnetopause: A combined global MHD and test‐particle study

Abstract: We study the spatiotemporal characteristics of energetic particle losses from the magnetosphere using test‐particle trajectories in electromagnetic fields from a global magnetosphere magnetohydrodynamic (MHD) simulation. We use a dynamically evolving distribution of high‐resolution electromagnetic fields from the Lyon‐Fedder‐Mobarry global MHD model and trace large ensembles of 100 keV hydrogen and oxygen ions as well as electrons from a near‐Earth plasma sheet location through their escape from the magnetosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 18 publications
3
66
1
Order By: Relevance
“…Figure illustrates that there is little low‐latitude entry near the subsolar point and that the vast majority of low‐latitude test particle entry, marked by the region between the green lines, occurs further downtail where the boundary becomes Kelvin‐Helmholtz unstable. This is the converse of the result discussed by Sorathia et al () where it is found that the egress of magnetospheric plasma is inefficient within 0400 hr of magnetic noon, or | ϕ E | ≤ 60°. These two results in tandem illustrate that boundary dynamics play an important role in regulating mass in the magnetosphere.…”
Section: Resultssupporting
confidence: 71%
“…Figure illustrates that there is little low‐latitude entry near the subsolar point and that the vast majority of low‐latitude test particle entry, marked by the region between the green lines, occurs further downtail where the boundary becomes Kelvin‐Helmholtz unstable. This is the converse of the result discussed by Sorathia et al () where it is found that the egress of magnetospheric plasma is inefficient within 0400 hr of magnetic noon, or | ϕ E | ≤ 60°. These two results in tandem illustrate that boundary dynamics play an important role in regulating mass in the magnetosphere.…”
Section: Resultssupporting
confidence: 71%
“…We propose that the local antiparallel reconnection in the vicinity of the cusps, such as observed by Nykyri, Otto, Adamson, Dougal, and & Mumme (), results into the formation of stronger magnetic field depressions (∼50–80 nT) than the component reconnection that was operating and created the elongated cavity for the present event. Our future work is to better understand the relative contributions of local physical mechanisms (e.g., acceleration via gradients in reconnection quasi‐potential, Nykyri et al, ; wave acceleration, Nykyri et al, ; and Kelvin‐Helmholtz Instability‐driven processes Moore et al, ; Sorathia et al, ) and remote sources (ring current, Pulkkinen et al, , and foreshock energetic particles, Trattner et al, ) contributing to these enhanced fluxes of energetic electrons and ions in these cavities. It is noteworthy that for the present event the IMF orientation and plasma conditions remained quite steady for hours, allowing reconnection site to remain relatively stable, and lead to formation of cavities along MMS trajectory.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Our modeling approach provides a realistic treatment of key physical processes necessary for capturing storm time variability of the outer electron belt including the following: Large dynamic magnetic field distortions across the inner magnetosphere due to the storm time RC, shown to be important for magnetopause losses (e.g., Ukhorskiy et al, , ). Magnetotail convection, including mesoscale flows, that can directly inject electrons into the outer belt (e.g., Kress et al, ). ULF waves induced by solar wind variations (i.e., density fluctuations and enhanced velocity; e.g., Claudepierre et al, ; Takahashi et al, ) that drive stochastic radial transport across the outer belt (e.g., Kress et al, ). Magnetopause boundary dynamics, for example, Kelvin‐Helmholtz instability (Merkin et al, ), that mediates electron escape rates (Sorathia et al, ). Explicit integration of electron trajectories necessary to capture nondiffusive stochastic transport (Ukhorskiy & Sitnov, ) and nonlinear effects such as magnetic trapping (Ukhorskiy et al, ). …”
Section: Introductionmentioning
confidence: 99%
“…• ULF waves induced by solar wind variations (i.e., density fluctuations and enhanced velocity; e.g., Claudepierre et al, 2015;Takahashi et al, 2016) that drive stochastic radial transport across the outer belt (e.g., . • Magnetopause boundary dynamics, for example, Kelvin-Helmholtz instability (Merkin et al, 2013), that mediates electron escape rates (Sorathia et al, 2017). • Explicit integration of electron trajectories necessary to capture nondiffusive stochastic transport (Ukhorskiy & Sitnov, 2008) and nonlinear effects such as magnetic trapping .…”
Section: Introductionmentioning
confidence: 99%